(untitled) (Jurnal Sejarah Indonesia, 2025)
The purpose of this study is to analyze the implementation of state power through civil government in carrying out abstract politics and concrete politics to realize national integration and identity. The method used is a literature study. The study shows that the government provides direction or produces abstract policies, as shown in the policy of adding new heroes from regions in Indonesia. This shows the government’s efforts to foster and strengthen the values ​​of patriotism, heroism, and a sense of belonging to the spirit of Indonesian nationality as the nation’s identity. Abstract policies do not refer to material objects. The output is happiness, honesty, freedom, involvement, and togetherness. Concrete policies include the development of integrated infrastructure, factories, industrial areas, services, and tourism to encourage economic growth, employment, and poverty alleviation. Both must occur in a balanced manner. Aspirations, hopes, and messages from the regions can be positive and strengthen the work done by the government, compared to negative responses that seem to deconstruct what the government has done, is doing, and will do.